Antiviral activities of pyrimidine nucleoside analogues: some structure--activity relationships - Dragún, M; Rada, B; Novotný, L; Beránek, J (Acta virologica, 1990)
Seventeen nucleoside derivatives (derived from arabinosylcytosine, resp. cytidine, 5-fluorouracil and uracil) were tested by agar-diffusion plaque-inhibition test for their antiviral activity with herpes simplex, vaccinia, fowl plague, Newcastle disease and western equine encephalomyelitis viruses. The highest antiviral activity against DNA viruses exhibited arabinosylcytosine, N4-acylarabinosylcytosines, arabinosylthiouracil, cyclocytidine and its 5'-chloroderivative. RNA viruses were inhibited by 5-fluorouridine only, whereas other tested compounds were ineffective or showing marginal activity only. By search for relationship between chemical structure and antiviral activity a tendency was found of higher antiviral activity at lower lipophilicity. This is probably due to better transport of the studied compounds into cell. The chemical structure, however, is the main reason of antiviral activity.
Keywords: virus vakcinie; pyrimidinové nukleosidy; Influenza A virus; Pyrimidine Nucleosides; Structure-Activity Relationship; virus newcastleské nemoci; antivirové látky; Vaccinia virus; vztahy mezi strukturou a aktivitou; Viral Plaque Assay; Animals; Antiviral Agents; Encephalitis Virus, Western Equine; zvířata; virus chřipky A; Newcastle disease virus; Simplexvirus; virus západoamerické encefalomyelitidy koní; plakové testy